2019
DOI: 10.1016/j.jpedsurg.2018.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism following inpatient pediatric surgery: Analysis of 153,220 patients

Abstract: Purpose: To evaluate venous thromboembolism (VTE) rates and risk factors following inpatient pediatric surgery.Methods: 153,220 inpatient pediatric surgical patients were selected from the 2012-2015 NSQIP-P database. Demographic and perioperative variables were documented. Primary outcome was VTE requiring treatment within 30 postoperative days. Secondary outcomes included length of stay (LOS) and 30-day mortality. Prediction models were generated using logistic regression. Mortality and time to VTE were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 53 publications
5
25
0
Order By: Relevance
“…Patients undergoing cardiothoracic surgery, however, were found to be at higher risk of VTE when compared with patients receiving general surgery. This is consistent with previous literature in pediatric surgery, which finds higher rates of VTE after cardiothoracic procedures 38…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients undergoing cardiothoracic surgery, however, were found to be at higher risk of VTE when compared with patients receiving general surgery. This is consistent with previous literature in pediatric surgery, which finds higher rates of VTE after cardiothoracic procedures 38…”
Section: Discussionsupporting
confidence: 93%
“…Longer operative time was independently associated with VTE, while patients with VTE also had longer hospitalizations. An association between hospital length of stay and VTE risk in children had been reported previously,7 17 29 as with operative time 12 13 38. These findings are further corroborated in the literature around VTE in adults, where studies have found that longer operative times39 and longer hospital stays39 are associated with VTE.…”
Section: Discussionsupporting
confidence: 75%
“…Bleeding and thrombosis in critically ill pediatric patients and those undergoing major surgery remains a complex clinical problem. 39 Increasingly, critically ill children and neonates are undergoing complex surgeries and interventions, but evidence-based, biology-informed guidelines for managing these patients are important. 79 Risk factors that can guide decision-making and therapeutic interventions in this population are scarce, 79 often largely extrapolated from adult practice, and do not account for special age-related changes.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 44 In an ACS National Surgical Quality Improvement Program–based study examining rates of venous thromboembolism (VTE) in pediatric surgery patients, Sherrod et al found that the highest VTE risk occurred in patients undergoing cardiothoracic or general surgical procedures, omphalocele repair, CSF-shunt creation, and complete colectomy via abdominal approach. 39 In a national study examining rates of femoral arterial thrombosis following cardiac catheterization in pediatric populations, we reported that infants aged 0 to 12 months have the highest rate of arterial thrombosis following cardiac catheterization of any pediatric age-group and that arterial thrombosis is associated with increased morbidity and cost when compared to children aged 1 to 18. 45 , 46 …”
Section: Clinical Problems Of Pediatric Bleeding and Thrombosismentioning
confidence: 97%
See 1 more Smart Citation